Keragaman Morfologi dan Kandungan Tanin pada Tanaman Leunca [Solanum nigrum (L.)] - Nadila, Dea; ,, Sobir; Syukur, dan Muhamad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Black nightshades [Solanum nigrum (L.)] is an indigenous vegetable originatied from tropical and subtropical regions. In Indonesia, black naightshades widely spread in Java, especially West Java. Black nightshades has a bitter taste caused by the content of tannins. The objective of this study was to identify and analyze the morphological and tannin content of 20 black nightshades accessions. The research was started with germplasm exploration in November 2015-February 2016, followed by planting and analysis until September 2016 at a laboratory of the Center for Tropical Horticultural Studies (PKHT) IPB. The experiment was arranged in a single-factor randomized complete block design with three replications. The results from cluster analysis based on morphological variability showed that the accessions of black nightshades can be grouped into two groups. The accessions had different fruit tannin contents, and some accessions can be selected for breeding material.Keywords: group analysis, indigenous vegetable, qualitative character, quantitative character